Occupational Balance and Financial Education in University Students who Develop Economic Activities to Support Themselves During Their Studies (Revista Electrónica Calidad en la Educación Superior, 2025)
A research study was conducted with students from the Fundación Universitaria del Área Andina in Colombia and the Universidad San Nicolás de Hidalgo in Mexico to explore their perceptions of entrepreneurship and money, as well as how they organize their income-generating activities in relation to their academic responsibilities. This qualitative and descriptive study utilized inquiry forms validated by experts and is part of an institutional project approved by the ethics committee of Areandina. The results showed that most participants value knowledge in personal finance and economic management as key to their labor and educational autonomy. They also recognize saving as essential for personal growth and achieving long-term goals, considering the historical social limitations faced by women in their personal finances and income generation.
Keywords: occupational balance; undergraduate female students; financial education